Synthesis of Cotton from Tossa Jute Fiber and Comparison with Original Cotton - Md. Mizanur Rahman; Md. Rezaur Rahman; Sinin Hamdan; Md. Faruk Hossen; Josephine Chang Hui Lai; Fui Kiew Liew (International Journal of Polymer Science)
Cotton fibers were synthesized from tossa jute and characteristics were compared with original cotton by using FTIR and TGA. The FTIR results indicated that the peak intensity of OH group from jute cotton fibers occurred at 3336 cm−1 whereas the peak intensity of original cotton fibers occurred at 3338 cm−1. This indicated that the synthesized cotton fiber properties were very similar to the original cotton fibers. The TGA result showed that maximum rate of mass loss, the onset of decomposition, end of decomposition, and activation energy of synthesized cotton were higher than original cotton. The activation energy of jute cotton fibers was higher than the original cotton fibers.